PENELITIAN DRAINASE JALAN RAYA (STUDI KASUS RUAS JALAN PALIMANAN – JATIBARANG KM - Syariman, Petrus (JURNAL SUMBER DAYA AIR, 2018)
Highways are often damaged by excessive water content below road surface. The road section between Palimanan - Jatibarang, West Java is an area often flooded particularly at left and right sides of road. To prevent floods, a study on these ditches had been implemented to determine the dimension of a ditch proportional with hydrological conditions in its vicinity. The method applied in this study had been the mapping of detailed highway situation, rainfall intensity analysis, design flood analysis, and flow discharge simulation using a HEC-HMS model. Study results showed that flow discharge passing through the out-let drainage is 3.88 m3/sec and 6.29 m3/sec respectively, for a return period of two and five years. With a flow velocity assumption of 1.2 m/sec and a cross sectional area of out-let drainage on site of 3.19 m2, inundation time at vicinity of out-let is respectively four hours for a return period of two years, and six and half hours for a return period of five years. The average cross sectional dimension recommended for a return period of two years is 1.36m x 2.0m, and for a return period of two years, 2.0 m x 2.0 m.